Pengaruh Gaya Kepemimpinan terhadap Kepuasan Kerja Tenaga Kesehatan di Fasilitas Pelayanan Kesehatan: Literature Review - Rifqa Masry; Josepin Karolina; Windi Audina; Annisa Zahra; Dimas Septiadi; Wasiyem Wasiyem (Pusat Riset dan Inovasi Nasional, 2026)
Health worker job satisfaction is an important aspect in supporting service quality and organizational performance. Various studies show that leadership styles such as transformational, participatory, situational, and supportive styles are strongly associated with increased job satisfaction. This study identified 10 articles published between 2020 and 2025 that met the inclusion criteria, including quantitative studies in various healthcare settings. The synthesis results state that transformational leadership consistently contributes positively to job satisfaction through increased motivation, communication, teamwork, and perceptions of organizational justice. Participative leadership also contributes to increased job satisfaction, although its effectiveness depends on the organizational context. Other factors such as organizational culture, work-life balance, self-efficacy, and work environment were also found to play a role as supporting or mediating variables. These findings emphasize that strengthening the capacity of leaders and implementing a supportive and inspiring leadership style are very important for improving the welfare of health workers and the quality of services. This study is expected to contribute as a reference in the development of managerial policies in health care facilities.